‘As for you, do not pray on behalf of this people’ Intercession, deception and shalom in the book of Jeremiah - Joerstad, Mari (2016)
A unique feature of the book of Jeremiah is God’s thrice repeated ban on intercession. In 7.16, 11.14 and 14.11, God forbids Jeremiah to pray on behalf of the people. In this article I explore how the ban on intercession connects with the Jeremian themes of falsehood and shalom. I argue that Jeremiah is not allowed to pray for the people because he must identify with God’s point of view. Intercession only becomes meaningful in Jeremiah as a means for the exiled people to learn that God is the source of their shalom.
Keywords: Bibel; Bibel; Bibel; Bibel